Always coming home - Le Guin, Ursula K., 1929-2018.; Barton, Todd; Chodos, Margaret; Hersh, George (Toronto ; New York : Bantam Books, 1986)
A rich interweaving of story, fable, and poetry which immerses the reader in the culture of Kesh, a peaceful people In the distant future who inhabit a place called the Valley on the Northern Pacific coast
"A Bantam Spectra book."
Keywords: Science fiction; Local author; novels; Novels; Fiction; Fiction; Novels; Romans